Mode II performance of toughened Elium composites - Foo, Wei Xiang (Nanyang Technological University, 2023)
Composite materials have been increasingly taking over traditional materials such as metals and plastics due to their ability to adapt to various applications, allowing them to effectively versatile in various industries such as aerospace, marine. ARKEMA developed a thermoplastic resin Elium®, a highly recyclable resin that both exists in liquid form and cures at room temperature, allowing the usage of liquid processing manufacturing procedures such as Vacuum Assisted Resin Infusion (VARI) which is carried out in this project. This Final Year Project presents an investigation on Mode II performance on toughened Elium® composites by using Elium®, Nanostrength® (NS) Elium® and Elium® with Clearstrength® XT-100 matrix systems, and Ultra High Molecular Weight Polypropylene (UHMWPP) and Polyester as fibre reinforcements. Results obtained from the Mode II tests showed that Elium® composites were able to achieve better peak load efficacy compared to Elium®-filler samples. They show better ability to avoid the manifestation of crack propagation, as well as hold off crack propagation in terms of stable load drops. Elium®-1% Clearstrength® XT-100, Elium®-2.5% Clearstrength® XT-100 and Nanostrength® Elium® composites are 2-6%, 11-36% and 40-50% lower than that of Elium® composites, respectively. Elium® composites have the highest Mode II fracture toughness values, followed by Elium®-1% Clearstrength® XT-100 with a slight drop by 7-8% in GIIc values. Elium®-2.5% Clearstrength® XT-100 and NS Elium®-based composites were among the least favourable by 18-43% and 65-69% lower respectively, when compared to Elium®-1% Clearstrength® XT-100. High Mode II fracture toughness is substantiated by extensive plastic deformation after shear loading, observed during fractographic analysis. Fractography analysis presented Elium® and Elium®-Clearstrength® XT-100 composites having signs of fibre pull-outs, river marks and matrix deformation, improving Mode II fracture toughness. NS Elium® composites had signs of bare fibres and fibre breakages which lowers Mode II fracture toughness.